Salmonella Infection Upregulates the Leaky Protein Claudin-2 in Intestinal Epithelial Cells - Zhang, Yong-guo (Public Library of Science, 2013)
BACKGROUND: Tight junctions seal the space between adjacent epithelial cells. Mounting evidence suggests that tight junction proteins play a key role in the pathogenesis of human disease. Claudin is a member of the tight junction protein family, which has 24 members in humans. To regulate cellular function, claudins interact structurally and functionally with membrane and scaffolding proteins via their cytoplasmic domain. In particular, claudin-2 is known to be a leaky protein that contributes to inflammatory bowel disease and colon cancer. However, the involvement of claudin-2 in bacterial infection in the intestine remains unknown. METHODS/PRINCIPAL FINDINGS: We hypothesized that Salmonella elevates the leaky protein claudin-2 for its own benefit to facilitate bacterial invasion in the colon. Using a Salmonella-colitis mouse model and cultured colonic epithelial cells, we found that pathogenic Salmonella colonization significantly increases the levels of claudin-2 protein and mRNA in the intestine, but not that of claudin-3 or claudin-7 in the colon, in a time-dependent manner. Immunostaining studies showed that the claudin-2 expression along the crypt-villous axis postinfection. In vitro, Salmonella stimulated claudin-2 expression in the human intestinal epithelial cell lines SKCO15 and HT29C19A. Further analysis by siRNA knockdown revealed that claudin-2 is associated with the Salmonella-induced elevation of cell permeability. Epithelial cells with claudin-2 knockdown had significantly less internalized Salmonella than control cells with normal claudin-2 expression. Inhibitor assays demonstrated that this regulation is mediated through activation of the EGFR pathway and the downstream protein JNK. CONCLUSION/SIGNIFICANCE: We have shown that Salmonella targets the tight junction protein claudin-2 to facilitate bacterial invasion. We speculate that this disruption of barrier function contributes to a new mechanism by which bacteria interact with their host cells and suggests the possibility of blocking claudin-2 as a potential therapeutic strategy to prevent bacterial invasion.